Self-Perceived Pain in Chinese Patients With Cancer - Zhang, Yongfu; Tan, Xiaomin; Li, Wengao; Wang, Hongmei; Sun, Hengwen; Liu, Ting; Zhang, Jingying; Zhang, Bin; Yang, Yuan (Frontiers in Psychology, 2019)
Background Pain is one of the most burdensome and prevalent symptoms cancer patient report and it has severe negative impact on patient’s quality of life. The aim of this study is to estimate the prevalence of pain and to test the association between demographic, clinical, psychological factors, and self-assessed pain in Chinese cancer population. Methods A total of 553 cancer patients were recruited in this cross-sectional study. Patient’s basic demographic data was collected by a study-designed information sheet, and patient’s pain, sleep disturbance and psychological distress were assessed by several validated measurements (MPQ-SF, AIS, FoP-Q-SF, PHQ-9, and GAD-7). Descriptive statistics and hierarchical multiple regression analyses were performed. Results Of the 553 patients, 411 (74.32%) patients reported that they experience some degree of pain. Fear of progression, anxiety, insomnia, and depressive symptoms were significantly associated with different subscales and the overall pain score in bivariate correlation matrix. Insomnia, depressive symptoms, and fear of cancer progression were significant independent factors of cancer pain on multivariate analyses. Conclusion Psychological factors play a great role in the relationship between objective pathophysiology and patient’s subjective experience of pain. It is important to evaluate each individual in detail with respect to psychological distress and pain severity when planning treatment and rehabilitation.